An efficient lactone-to-lactam conversion for the synthesis of thiophene Pechmann lactam and the characterization of polymers thereof. Issue 42 (4th October 2018) - Lee, Kyu Cheol; Lee, Hae Rang; Kang, So-Huei; Lee, Jungho; Park, Young IL; Noh, Seung Man; Oh, Joon Hak; Yang, Changduk
Abstract : We proposed an efficient methodology for Pechmann lactone-to-lactam conversion for various molecular applications. Abstract : Despite having unique structural features, e.g., high co-planarity and a strong polar bicyclic lactam structure, thiophene bipyrrolylidene-2, 2′(1 H, 1′ H )-dione (TBPD) has been less explored as a dye, mainly due to the quite low yield in its synthesis via lactone-to-lactam conversion. We reported an efficient methodology for synthesizing TBPD in high yield using p -toluenesulfonic acid monohydrate and a catalytic amount of 4-dimethylaminopyridine in the chloroform solvent. From the newly synthesized series of TBPD-based donor–acceptor-type polymers, we fabricated organic field-effect transistors (OFETs), which were subjected to a systematic study on the relationship between film microstructure and charge transport. Among them, the annealed PTBPD-Th film revealed a more ordered lamellar packing with the highest number of interlayers and preferential edge-on orientation, yielding the best hole mobility (up to 0.46 cm 2 V −1 s −1 ). The improved synthesis of TBPD and our findings concerning related polymers could promote further research and development associated with the TBPD unit.